1997
DOI: 10.1159/000099879
|View full text |Cite
|
Sign up to set email alerts
|

Brain Glucose Metabolism with [<sup>18</sup>F]-Fluorodeoxyglucose and Positron Emission Tomography before and after Surgical Resection of Epileptogenic Cavernous Angiomas

Abstract: Surgery of cavernous angiomas is often proposed due to the epileptogenic and hemorrhagic potential of this lesion. Little information is available on the impact of surgical resection on brain metabolism, locally or at a distance from the lesion. Fifteen patients presenting with a cavernoma and epileptic seizures underwent positron emission tomography examinations before and 1 year after surgical resection. We studied the quantitative cerebral metabolic rate of glucose (CMRGlu) with [18F]-fluorodeoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…These changes could represent a ‘release’ phenomenon with reversal of a functional or metabolic disruption. Functional imaging studies such as fluorodeoxyglucose-PET showed a normalization of glucose metabolism in the ipsilateral temporal cortex ( Gogoleva et al , 1997 ), inferior frontal lobe, thalamus and parietal lobe ( Spanaki et al , 2000 ; Takaya et al , 2009 ) following temporal lobe surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These changes could represent a ‘release’ phenomenon with reversal of a functional or metabolic disruption. Functional imaging studies such as fluorodeoxyglucose-PET showed a normalization of glucose metabolism in the ipsilateral temporal cortex ( Gogoleva et al , 1997 ), inferior frontal lobe, thalamus and parietal lobe ( Spanaki et al , 2000 ; Takaya et al , 2009 ) following temporal lobe surgery.…”
Section: Discussionmentioning
confidence: 99%
“…FDG-PET shows a normalization of glucose metabolism in the remaining ipsilateral temporal cortex (Gogoleva et al, 1997) and extratemporal regions including the inferior frontal lobe, thalamus and parietal lobe (Spanaki et al, 2000; Takaya et al, 2009) following surgery. Moreover, magnetic resonance spectroscopy shows that N-acetylaspartate (NAA)/creatine (Cr) ratios normalize in the ipsilateral (Cendes et al, 1997; Serles et al, 2001) and contralateral (Hugg et al, 1996; Lantz et al, 2006) temporal cortex in patients rendered seizure free by surgery.…”
Section: Discussionmentioning
confidence: 99%
“…3) The perilesional hemosiderin-laden parenchyma is the cause of seizures in most cases. 6) On the other hand, more than 90% of patients with infratentorial cavernomas have neurological improvement. 14) To date, only four cases of multiple simultaneous hemorrhages in cavernomas have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%